Answer:
10
Step-by-step explanation:
give me brainly
am i correct? let me know
Answer:
y = 4 + -2x
Step-by-step explanation:
Simplifying
y = -2x + 4
Reorder the terms:
y = 4 + -2x
Solving
y = 4 + -2x
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Simplifying
y = 4 + -2x
Answer:
y = 3/4x + 19
Explanation:
First we need to write the equation in the form y=mx+c:
3x-4y=6
-4y=-3x+6
y=3/4x-3/2
Because the lines are parallel, we can deduce that the gradients (m) are equal. That means that the gradient of our new equation will also be 3/4.
We will now use the following equation:
y - y1 = m(x - x1)
We will substitute in the new line’s gradient as well as the coordinates we were given:
y - 10 = 3/4(x + 12)
Now we solve this equation into the form y=mx+c:
y - 10 = 3/4x + 9
y = 3/4x + 19
Answer:
23/100
Step-by-step explanation:
Answer:
the probability that a real emergency situation exists is 0.16 (16%)
Step-by-step explanation:
defining the event A= the alarm sounds ,we have
P(A)= probability that an emergency situation exists * probability that the alarm sounds given that an emergency situation exists + probability that a emergency situation does not exist * probability that the alarm sounds given that an emergency situation does not exist = 0.004* 0.95+ 0.996 * 0.02 = 0.02372
then if we use the theorem of Bayes for conditional probability and define the event E= a emergency situation exists , then
P(E/A)= P(E∩A)/P(A)= 0.004* 0.95/0.02372 =0.16 (16%)
where
P(E∩A)= probability that an emergency situation exists and the alarm sounds
P(E/A) = probability that an emergency situation exists given that the alarm has sounded